Comparative Analysis of Dry-EDM and Conventional EDM in machining of Hastelloy - et.al, Apurva A Kulkarni (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Dry EDM may be a modification of the traditional electrical discharge machining (EDM) process during which the liquid dielectric is replaced by a gaseous medium. High velocity gas is supplied through it into the discharge gap. The flow of high velocity gas into the gap facilitates removal of debris and prevents excessive heating of the tool and work piece at the discharge spots. it's now known that aside from being an environment–friendly process, other advantages of the dry EDM process are low tool wear, lower discharge gap, lower residual stresses, smaller white layer and smaller heat affected zone.[1] Keeping literature review into consideration, during this research, an effort has been made by selecting compressed gas as a dielectric medium, with Hastelloy as a work piece material and copper as a tool electrode. Conventional experiments were also performed. Experiments are performed using Taguchi DoE orthogonal array to watch and analysis the consequences of various process parameters to optimize the response variables like material removal rate (MRR) and gear wear rate (TWR).